2023
DOI: 10.1186/s13756-023-01278-0
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-resistant enterococci (VRE) in hospital settings across European borders: a scoping review comparing the epidemiology in the Netherlands and Germany

Abstract: The rising prevalence of vancomycin-resistant enterococci (VRE) is a matter of concern in hospital settings across Europe without a distinct geographical pattern. In this scoping review, we compared the epidemiology of vancomycin-resistant Enterococcus spp. in hospitals in the Netherlands and Germany, between 1991 and 2022. We searched PubMed and summarized the national antibiotic resistance surveillance data of the two countries. We included 46 studies and summarized national surveillance data from the NethM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 90 publications
1
4
0
Order By: Relevance
“…Our findings revealed that VRE constituted 15.9% of the total sample, while VSE made up 84.1%. This VRE incidence was consistent with recent studies [ 12 , 13 ]. The highest incidence of VRE was observed in E. casseliflavus (75%), followed by E. gallinarum (50%).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings revealed that VRE constituted 15.9% of the total sample, while VSE made up 84.1%. This VRE incidence was consistent with recent studies [ 12 , 13 ]. The highest incidence of VRE was observed in E. casseliflavus (75%), followed by E. gallinarum (50%).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, 77% of E. faecium isolates were VRE. The prevalence of VRE colonization in different patient groups was investigated in nine cross-sectional studies, two cohort studies and one pre-post study in hospitals in Europe [29]. The prevalence ranged between 1.2% and 27.7% [21].…”
Section: Discussionmentioning
confidence: 99%
“…VRE continues to be a serious issue in healthcare due to the few available treatment options and rising prevalence of VRE in Europe. Effective strategies to control the spread of VRE are required [29].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Enterococcus spp. to acquire additional resistance via, e.g., mobile genetic elements or sporadic chromosomal mutations, raises concerns about the available therapeutical options for the treatment of enterococcal infections [12,13]. Vancomycin-resistant E. faecium (VRE) isolates have been recognized as high-priority pathogens by the World Health Organization, for which new antibiotics are urgently needed, and the increasing prevalence of VRE has been reported in hospitals in Europe [14,15].…”
Section: Introductionmentioning
confidence: 99%